2015
DOI: 10.1002/jctb.4851
|View full text |Cite
|
Sign up to set email alerts
|

High activity and regenerability of a palladium–gold catalyst for chloroform degradation

Abstract: BACKGROUND: Chloroform (CF), a common groundwater contaminant, can be degraded in deionized water reductively using Pd and Pd-Au catalysts under mild conditions (room temperature, atmospheric pressure) via hydrodechlorination (HDC). However, the performance of these catalysts under field-like conditions is unknown. This study evaluates the lab-scale performance and optimal operating conditions for flow reactors using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…13,37 The fouled catalysts should be regenerable by flushing the reactor bed with a bleach (e.g., sodium hypochlorite) solution. 35,38 The simulated HFPW showed a stronger deactivation effect than DI water, which is most likely due to scale formation from the calcium in the water and the CO 2 in the inlet ambient air stream.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,37 The fouled catalysts should be regenerable by flushing the reactor bed with a bleach (e.g., sodium hypochlorite) solution. 35,38 The simulated HFPW showed a stronger deactivation effect than DI water, which is most likely due to scale formation from the calcium in the water and the CO 2 in the inlet ambient air stream.…”
Section: Resultsmentioning
confidence: 99%
“…The phenol degradation rate constant using Pd/Al 2 O 3 catalyst in simulated HFPW (8.1 × 10 –4 min –1 ) decreased to 62% of that in DI water (5.0 × 10 –4 min –1 ) (Table ). The nonzero performance decay rate constant could be due to the fouling of the catalyst surface (i.e., blocking of the catalytic active sites) over time by carbonaceous deposits, mainly of condensation/polymerization byproducts formed from oxidative coupling side reactions. , The fouled catalysts should be regenerable by flushing the reactor bed with a bleach (e.g., sodium hypochlorite) solution. , The simulated HFPW showed a stronger deactivation effect than DI water, which is most likely due to scale formation from the calcium in the water and the CO 2 in the inlet ambient air stream.…”
Section: Resultsmentioning
confidence: 99%
“…Testing the reaction over larger particles showed a particle size effect: increasing the size of the Au NP core from 4 to 7 nm led to a decrease in the rate for NPs with identical Pd sc% due to less subsurface Pd migration into the smaller NPs. 28 Pd-on-Au NPs were shown to be effective for a number of different CVOCs, including PCE, 29 CF, 30,31 and DCE. 29 Catalysis fundamentals can also be learned from the surfacebound transition species.…”
Section: Heterogeneous Hydrogenation Catalysismentioning
confidence: 99%
“…69 We also tested Pd supported on alumina ("Pd/Al 2 O 3 ") and PdAu/Al 2 O 3 catalysts on CFcontaminated groundwater. Because the HDC reaction generates HCl, a combination of lower pH and generation of Cl − initially led to catalyst fouling, 31 which was amended with citrate additive. While deactivation was observed, it was reversible via exposure to bleach followed by reduction with aqueous H 2 .…”
Section: Implementation and Perspectivementioning
confidence: 99%
“…The bimetallic catalysts had smaller metal particles and larger numbers of exposed active sites than those of monometallic catalysts. (Zhou et al, 2016) (Velazquez et al, 2016) It was shown that the bimetallic catalyst outperformed the monometallic Pd catalyst. The same authors reported activity of this material in hydrodechlorination of trichloroethylene and perchloroethylene over PdAu catalysts to a single-carbon organohalide.…”
Section: Hydrodechlorination (Hdc)mentioning
confidence: 99%